1995
DOI: 10.1007/bf00311528
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal lavage versus drainage for perforated appendicitis in children

Abstract: A total of 231 children with acute appendicitis were treated at our hospitals during the 10 years between 1984 and 1993, 53 of whom had a perforated appendix. These 53 patients were randomly assigned to two groups at the time of surgery according to the different procedures performed. Thus, 29 children were managed by appendectomy followed by peritoneal lavage using a large amount of saline, and intravenous antibiotic therapy consisting of aminoglycoside and cephem (lavage group), while the other 24 children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Nevertheless, the role of this practice remains an ongoing matter of debate [17][18][19][20][21][22][23][24][25]. Routine drainage of the abdominal cavity after various types of surgical interventions has been a robust dogma in abdominal surgery for many decades.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the role of this practice remains an ongoing matter of debate [17][18][19][20][21][22][23][24][25]. Routine drainage of the abdominal cavity after various types of surgical interventions has been a robust dogma in abdominal surgery for many decades.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the included studies were RCTs; the remainder were retrospective cohort studies. Four studies included analysis only of the paediatric population, two of which were performed entirely using open surgery. The age of the population was poorly reported throughout.…”
Section: Resultsmentioning
confidence: 99%
“…The age of the population was poorly reported throughout. There was a high degree of variation between pathological findings at surgery, with some studies , analysing the outcomes only of patients with complex appendicitis (perforation, gangrene, localized abscess) , whereas the remaining studies included patients with simple appendicitis (inflammation in the appendix alone). In some studies drains were never used as part of local institutional policy, whereas drains were used in the remaining studies at the discretion of the operating surgeon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toki et al reported that peritoneal lavage with 1 000-8 000 ml of saline was better than tube drainage for the management of perforated appendicitis in children. 6 Thus, we are attempting to minimize the use of tube drainage in consideration of their results and our recent experience. We also recommend that if an initial physical examination and a high CRP value indicate acute appendicitis in a child, further investigations should be done, and appropriate management initiated as early as possible.…”
Section: Discussionmentioning
confidence: 99%